The Influence of Motivation, Needs, and Access to Information on Family Financial Planning in Life Insurance Purchasing - Istikhamah - Istikhamah; Lilik Noor Yuliati (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2016)
Every human needs safety and security in which one does not feel worried in their life. The same thing happens within family. This entity should be able to manage of its material resources in order to achieve the future goals. One of the managerial tools is financial planning in life insurance purchasing as life insurance is a way to get security in family life. The study aimed to analyze the influence of motivation, needs, and information access on financial planning in life insurance purchasing within family. Participants were 84 family members, either husbands or wives who did family financial planning and were selected using simple random sampling technique. The data were collected by interview using structured questionnaires. The findings indicated that family with motivation and needs of safety and security was more likely to do financial planning in life insurance purchasing.